First detection of Anaplasma phagocytophilum and Babesia divergens and high infection rates of Anaplasma marginale and Babesia bigemina in cattle in extensive grazing systems of Central Spain - Calleja Bueno, Lydia; Sainz, Ángel; García Sancho, Mercedes; González Martín, Juan V.; Díaz Regañón, David; Rodríguez Franco, Fernando; Agulla, Beatriz; Tormo, Bárbara; Villaescusa, Alejandra (My University, 2024)
Bovine vector-borne diseases have a considerable economic impact worldwide and affect health of humans and animals. However, different aspects of their epidemiology and their pathogenesis remain unclear. Despite the frequent description of clinical cases reported by practitioners attending cattle from Madrid, Central Spain, molecular prevalence of Anaplasma spp. and Babesia spp. has not been described. The aim of this study was to assess the positivity rate of A. phagocytophilum, A. marginale, A. centrale, B. bigemina andB. divergensin livestock of this area and to evaluate the existence of associations between these pathogens and haematological, biochemical and epidemiological data. Babesia divergens and A. phagocytophilum were detected for the first time in cattle from Madrid. Their positivity percentages were low (2.2% ± 1.4% and 1.8% ± 1.2%, respectively), but this description is of special interest, as these agents are potentially zoonotic. Both agents were found in areas of higher altitude and relative humidity and lower temperature. The detection of ticks in livestock during the moment of sampling was confirmed as a risk factor for these infections. Anaplasma marginale showed the highest molecular infection rate (30% ± 4.1%) in this study, followed by B. bigemina (21.9% ± 3.7%). Higher positivity rates of A. marginale and B. bigemina were found in the areas of mountain climate and warm-summer continental Mediterranean climate. The use of ectoparasiticide treatment was found as a risk factor for infection by A. marginale and B. bigemina. This finding could lead to reconsider the ectoparasiticide protocols that are used nowadays. Grazing on pastures with domestic or wild ruminants and the presence of wild carnivores were associated with higher rates of infection by these four agents and coinfections were frequently found. KEYWORDS anaplasmosis, babesiosis, cattle, infection rates, PCR, Spain
Keywords: anaplasmosis, babesiosis, cattle, infection rates, PCR, Spain